2017
DOI: 10.1002/joc.5249
|View full text |Cite
|
Sign up to set email alerts
|

Observational uncertainty and regional climate model evaluation: A pan‐European perspective

Abstract: The influence of uncertainties in gridded observational reference data on regional climate model (RCM) evaluation is quantified on a pan‐European scale. Three different reference data sets are considered: the coarse‐resolved E‐OBS data set, a compilation of regional high‐resolution gridded products (HR) and the European‐scale MESAN reanalysis. Five high‐resolution ERA‐Interim‐driven RCM experiments of the EURO‐CORDEX initiative are evaluated against each of these references over eight European sub‐regions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
124
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 81 publications
7
124
0
1
Order By: Relevance
“…Section 2 describes the data and methods used. Details on the data can also be found in Kotlarski et al (), on the downscaling methods, predictor variables, and the validation setup in Gutiérrez et al (). Section 3 presents the results of the validation of extremes.…”
Section: Introductionmentioning
confidence: 99%
“…Section 2 describes the data and methods used. Details on the data can also be found in Kotlarski et al (), on the downscaling methods, predictor variables, and the validation setup in Gutiérrez et al (). Section 3 presents the results of the validation of extremes.…”
Section: Introductionmentioning
confidence: 99%
“…Kotlarski et al . () evaluated a suite of RCMs against three different gridded reference data sets. They found that the uncertainty inherent in these datasets was typically smaller than climate model uncertainty.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the evaluation of downscaling methods, VALUE also addressed the quality of observational datasets used as reference for the evaluation (Kotlarski et al ., ; Herrera et al ., submitted manuscript, ). Kotlarski et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the seNorge2 daily mean temperature dataset has been described in the paper by Lussana et al (2018). Despite being released only recently, seNorge2 has already been used in a few applications, such as snow and permafrost mapping (Gisnås et al, 2017) and evaluation of climate projections (Kotlarski et al, 2017). Most noticeably, the Norwegian Water Resources and Energy Di-rectorate (NVE) uses seNorge2 as meteorological forcing for the national forecasting system for floods, avalanches and landslides.…”
Section: Introductionmentioning
confidence: 99%